The production-comprehension interface in second language acquisition an integrated encoding-decoding model - Lenzing, Anke 1973- (Bloomsbury Academic, 2022)
"This book explores the relation between second language (L2) production and comprehension at the level of processing. Proposing an 'Integrated Encoding-Decoding Model' of SLA, Anke Lenzing presents the results of a comprehensive empirical study to demonstrate the extent to which the two modalities rely on shared representations and/or shared processes. Through this detailed analysis, she sheds new light on the cognitive architecture of human language processing and offers a deeper understanding of the mechanisms at work in the L2 acquisition process"--
Keywords: Second language acquisition / Research / Methodology; Second language acquisition / Evaluation / Methodology; Sprachproduktion; Sprachverarbeitung -- Psycholinguistik; Sprachverstehen; Fremdsprachenlernen